1996
DOI: 10.1002/(sici)1096-9861(19960812)372:1<111::aid-cne8>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ?2A-adrenergic receptor-like immunoreactivity in the rat central nervous system

Abstract: In this study, we analyzed immunohistochemically the distribution of the A subtype of alpha 2-adrenergic receptor (alpha 2A-AR) in the rat central nervous system using light level immunohistochemistry. By using affinity-purified antisera, we found perikaryal labeling was diffuse and/or punctate; immunoreactive puncta were heterogeneous in size and number in a region-specific manner. Dense deposits of immunoreaction product were found associated with neuropil also, particularly in the lateral parabrachial nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
109
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 218 publications
(121 citation statements)
references
References 36 publications
12
109
0
Order By: Relevance
“…[ 3 H]RX821002 binding has been reported to recognize the α2A and α2C subtypes of the adrenergic receptor, whereas [ 125 I]-p-iodoclonidine is more selective for the α2A form (Wallace et al, 1994). High levels of the α2A-adrenergic receptor and its mRNA are present in the LC (McCune et al, 1993;Nicholas et al, 1993;Scheinin et al, 1994;Talley et al, 1996), where it functions as an autoreceptor on NE neurons (Norenberg et al, 1997;Callado and Stamford, 1999). Low levels of the α2C subtype are expressed in the LC, yet higher density occurs in other regions including cerebral cortex (McCune et al, 1993;Nicholas et al, 1993;Scheinin et al, 1994;Rosin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 H]RX821002 binding has been reported to recognize the α2A and α2C subtypes of the adrenergic receptor, whereas [ 125 I]-p-iodoclonidine is more selective for the α2A form (Wallace et al, 1994). High levels of the α2A-adrenergic receptor and its mRNA are present in the LC (McCune et al, 1993;Nicholas et al, 1993;Scheinin et al, 1994;Talley et al, 1996), where it functions as an autoreceptor on NE neurons (Norenberg et al, 1997;Callado and Stamford, 1999). Low levels of the α2C subtype are expressed in the LC, yet higher density occurs in other regions including cerebral cortex (McCune et al, 1993;Nicholas et al, 1993;Scheinin et al, 1994;Rosin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our results point to the a 2A AR being the prime receptor subtype mediating the suppressant action of dexmedetomidine on discrete cue and contextual fear learning. a 2A ARs are expressed in the amygdala where they are located on both the postsynaptic amygdala neurons or presynaptically on noradrenergic terminals (Talley et al, 1996). Immunocytochemical studies of the rat brainstem have shown that a 2A receptors are found on the axon terminals and dendrites of noradrenergic locus coeruleus neurons that project to the lateral and basolateral amygdala nuclei (Lee et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…21,25 Briefly, the ␣ 2C -AR gene was inactivated in 129/Sv embryonic stem cells 31 which were injected into C57BL/6J blastocysts, and the resulting chimeric mice were bred to F 1 (C57BL/6J × DBA/2J) animals. These animals were back-crossed for several generations to C57BL/6J mice; then intercrossed, and the tested ␣ 2C -KO mice were offspring of closely related F [11][12] pairs, which were combinations of mice with wild-type, heterozygous or homozygous genotypes for the ␣ 2C -AR mutation. All tested ␣ 2C -KO mice were homozygous for the mutation.…”
Section: Animalsmentioning
confidence: 99%
“…6 The three cloned ␣ 2 -AR subtypes, designated as ␣ 2A , ␣ 2B , and ␣ 2C , are well conserved across species and have distinct tissue and cellular distributions. [7][8][9][10][11][12] All ␣ 2 -AR subtypes couple to inhibitory G-proteins, but also differCorrespondence: Dr J Sallinen, Orion Corporation, Orion Pharma, PO Box 425, FIN-20101 Turku, Finland. E-mail: jukka.sallinen@ orion.fi Received 29 October 1998; revised 7 January and 16 February 1999; accepted 16 February 1999 ences have been demonstrated in their intracellular coupling and trafficking.…”
Section: Introductionmentioning
confidence: 99%